Genetic Diversity of Three Types of Curcuma Using Molecular Sequence-Related Amplified Polymorphism Markers - Setyawati, Andriyana; Samanhudi, Samanhudi; Bachtiar, Zuraida Anniswa (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
The genus Curcuma comprises numerous species with high medicinal value, many exhibiting morphological similarities that complicate taxonomic identification and hinder breeding efforts. This study aimed to elucidate the genetic diversity and relationships among three closely related species, Curcuma longa (turmeric), Curcuma purpurascens (temu tis), and Curcuma mangga using Sequence-Related Amplified Polymorphism (SRAP) markers. Genetic material was extracted from rhizome samples and amplified using five SRAP primer combinations, producing 56 loci with an average polymorphism percentage of 69.64%. The result showed a high genetic similarity (82%) between C. longa and C. purpurascens, whereas C. mangga exhibited a more distant relationship (55% similarity), indicating a narrower genetic base among the former two species. Additionally, total flavonoid content and antioxidant activity, with turmeric showing the highest flavonoid concentration (25.95% w/w), and C. mangga exhibiting the strongest antioxidant activity (42.12% wb). These findings highlight the effectiveness of SRAP markers in differentiating morphologically similar species and provide valuable genetic and phytochemical insights to support the conservation, breeding, and pharmacological development of Curcuma species. Integrating molecular and biochemical data underscores the potential for selecting superior varieties for both agricultural and medicinal applications.